2020
DOI: 10.1155/2020/3836172
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Functional Ingredients in Barley to Combat Human Chronic Diseases

Abstract: Barley plays an important role in health and civilization of human migration from Africa to Asia, later to Eurasia. We demonstrated the systematic mechanism of functional ingredients in barley to combat chronic diseases, based on PubMed, CNKI, and ISI Web of Science databases from 2004 to 2020. Barley and its extracts are rich in 30 ingredients to combat more than 20 chronic diseases, which include the 14 similar and 9 different chronic diseases between grains and grass, due to the major molecular mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 211 publications
0
66
0
Order By: Relevance
“…Polyphenols are bioactive compounds that extensively existed in plant foods and have many health-promoting effects by the different mechanisms, such as antioxidation, anti-inflammation, immunomodulation, and modulating gut microbiota [11,13]. Resveratrol is a natural phenolic compound and has been found in many foods, such as grapes, peanuts, blueberries, and red wine.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols are bioactive compounds that extensively existed in plant foods and have many health-promoting effects by the different mechanisms, such as antioxidation, anti-inflammation, immunomodulation, and modulating gut microbiota [11,13]. Resveratrol is a natural phenolic compound and has been found in many foods, such as grapes, peanuts, blueberries, and red wine.…”
Section: Introductionmentioning
confidence: 99%
“…Interaction studies demonstrated the binding of RSV to various F I G U R E 1 Chemical structure of trans-and cis-resveratrol (from Gambini et al, 2015) targets including tubulin, protein kinase C alpha (PKCα), phosphodiesterase-4D, human oral cancer cell line proteins, DNA sequences having AATT/TTAA segments, PKCα, lysine-specific demethylase 1 (Kataria & Khatkar, 2019). Furthermore, RSV targets multiple intracellular signalling substances and pathways including adenosine monophosphate kinase, nuclear factor-κB, inflammatory prostaglandins and cytokines, anti-oxidant enzymes-regulators of apoptosis, mitochondrial biogenesis, gluconeogenesis and lipid metabolism (Meng et al, 2021;Moraes, Moreira, Andrade, & Santos, 2020;Pannu & Bhatnagar, 2019;Zeng et al, 2020). These target molecules can be intracellular mediators of RSV action, although the mediatory role of some of them still require experimental confirmation.…”
Section: Mechanisms Of Rsv Actionmentioning
confidence: 99%
“…This can open up opportunities for discussions and for industrial sectors to retain some value and benefits in the final products in the GVCs market. However, food health effects [65] should be investigated to incorporate SDGs' good health and wellbeing targets.…”
Section: Limitationsmentioning
confidence: 99%